STRATEGI PENGEMBANGAN AGROWISATA BERBASIS AGROINDUSTRI KOPI DI PROVINSI BENGKULU - Syamsuwarni Rambe; Sapta Raharja; Faqih Udin (AGROINTEK, 2021)
Coffee is one of the leading commodities in Bengkulu Province. The Agricultural Technology Research Center (BPTP 2014) said Bengkulu Province was one of the top three producers of Indonesian coffee, therefore Bengkulu Province was suitable for agro-tourism development, but in its development agro-tourism would be left behind if it could not innovate according to market trends. Research objectives: to find a strategic location for the development of agro-tourism as well as the right strategy in developing agro-tourism based on the coffee agro-industry. The method used: the method of observation / descriptive analysis, the selected districts will be analyzed the development strategy with the SWOT analysis method Result: the calculation of the LQ method shows that Kepahiang Regency was chosen to be the location for agro-tourism development because the LQ value is 1.049, if the LQ value 1 the area is considered capable of exporting products exit the area. The position of developing agro-tourism in Kepahiang district is currently in quadrant II. This position shows that agro-tourism is already strong, but still faces big challenges. Agro-tourism must continue to diversify its strategies in order to face future threats. The results of the SWOT analysis produce 8 alternatives: Maintain the quality of the coffee produced so that consumer confidence is guaranteed, and tourists will come to visit again. 2) Maintaining the beauty around the tea plantations, by cooperating with the tea plantation managers. 3) Looking for investors who want to invest in agro-tourism as partners. 4) Review agro-tourism institutional management, increase promotional activities to increase market demand. 5) Maintaining characteristics and quality to avoid disappointment of coffee consumers. 6) Increasing the number of coffee processing industries due to abundant resources. 7) Increase the number of training sessions in collaboration with the Government and related agencies to improve the skills of both coffee processing workers and coffee farmers. 8) Improve facilities and infrastructure in order to defend agro-tourism from losing visitors.